Lama2 And Samsn1 Mediate the Effects of Brn4 on Hippocampal Neural Stem Cell Proliferation and Differentiation - Lei Zhang; Xunrui Zhang; Ruijie Ji; Yaya Ji; Yuhang Wu; Xiuyu Ding; Zhiying Shang; Xueyuan Liu; Wen Li; Jingjing Guo; Jue Wang; Xiang Cheng; et al. (Hindawi Limited, 2023)
The transcription factor Brn4 exhibits vital roles in the embryonic development of the neural tube, inner ear, pancreas islet, and neural stem cell differentiation. Our previous studies have shown that Brn4 promotes neuronal differentiation of hippocampal neural stem cells (NSCs). However, its mechanism is still unclear. Here, starting from the overlapping genes between RNA-seq and ChIP-seq results, we explored the downstream target genes that mediate Brn4-induced hippocampal neurogenesis. There were 16 genes at the intersection of RNA-seq and ChIP-seq, among which the Lama2 and Samsn1 levels can be upregulated by Brn4, and the combination between their promoters and Brn4 was further determined using ChIP and dual luciferase reporter gene assays. EdU incorporation, cell cycle analysis, and CCK-8 assay indicated that Lama2 and Samsn1 mediated the inhibitory effect of Brn4 on the proliferation of hippocampal NSCs. Immunofluorescence staining, RT-qPCR, and Western blot suggested that Lama2 and Samsn1 mediated the promoting effect of Brn4 on the differentiation of hippocampal NSCs into neurons. In conclusion, our study demonstrates that Brn4 binds to the promoters of Lama2 and Samsn1, and they partially mediate the regulation of Brn4 on the proliferation inhibition and neuronal differentiation promotion of hippocampal NSCs.